Yield perceptions, determinants and adoption impact of on farm varietal mixtures for common bean and banana in Uganda - Nankya, R.; Mulumba, John W.; Caracciolo, Francesco; Raimondo, M.; Schiavello, F.; Gotor, Elisabetta; Kikulwe, Enoch Mutebi; Jarvis, Devra I. (MDPI, 2017)
Crop variety mixtures (different varieties of a crop grown together in a single plot) have been successfully deployed in pathogen and pest management for several crops including wheat, common bean and rice. Despite the available evidence, promotion of this approach has remained limited in many countries, including Uganda. The factors that influence farmers’ adoption of varietal mixtures for common bean and banana were assessed, as well as the perceptions of farmers on the effects of mixtures on yields, through household surveys and statistical modelling. A three-year yield increase in both common bean and banana varietal mixtures in farmer fields, of 5.2% and 28.6%, respectively, is realized using robust OLS estimates. The study reveals that accessing knowledge on the importance of crop varietal mixtures and the skills relating to the approach are crucial for their adoption. Location of the farm significantly determined the perceived yield change, which calls for more research into mixtures’ suitability under particular contexts in respect to compatibility of genotypes, management practices and appropriate acreage for maximum impact. The positive effects of mixtures on yields make it an effective bioeconomy strategy. Policies that minimize the adoption barriers could improve the adoption of crop varietal mixtures on a wider scale.